Kompetensi Pengadilan Agama (PA) dalam Penyelesaian Sengketa Ekonomi Syariah (Telaah atas UU No. 3 Tahun 2006 tentang Pengadilan Agama dan UU Nomor 21 Tahun 2008 Tentang Perbankan Syariah) - Aji Damanuri (Justicia Islamica, 2014)
The settlement of shari'ah economic disputes according to Law No. 3 of 2006 concerning Religious Courts is the absolute competence of the Religious Courts as a litigation institution in the judicial environment. While the settlement of shari'ah economic disputes according to Law No. 21 of 2008 concerning shari'ah banking can be done through the Religious Court and or the General Court depending on the agreement contained in the contract of the parties. The dualism of judicial competence in shari'ah economic disputes between Law No. 3 of 2006 concerning Religious Courts and Law No. 21 of 2008 concerning Shari'ah Banking shows the weakness of lawmakers, especially in the field of shari'ah economics. The dualism of competence not only reduces the competence of the Religious Court as the holder of absolute competence, but also creates legal uncertainty. Vertically the order of legislation in Indonesia and horizontally both have the same position, so that the principle of nasah mansukh or the principle of Lex Posterior Derogat Legi Priori can be done.